PERANAN KEMASAN DAN MEDIA SIMPAN TERHADAP KETAHANAN VIABILITAS DAN VIGOR BENIH NANGKA (Artocarpus heterophyllus Lamk) KULTIVAR TULO-5 SELAMA PENYIMPANAN - Lodong,Yohanes Tambing, Adrianton, Oktralixon (AGROTEKBIS, 2015)
Jackfruit seed including recalcitrant seeds that can not be stored longer, and its high water content immediately germinate, so rapidly lose viability within a relatively short time. So that need special handling in maintaining viability and vigor during storage. This study aimed to obtain the type of packaging and appropriate storage media to maintain viability and vigor jackfruit seeds during storage. This study used a completely randomized design factorial two factors. The first factor is the packaging Basket woven bamboo, Box Styrofoam and cardboard box. The second factor is media store sawdust, rice husk and wood charcoal powder. The results showed that the use of packaging baskets woven bamboo and rice husk media play a role both in maintaining the viability and vigor of jackfruit Tulo-5 to generate higher seed moisture content that is on average 59.93%. Time germinate faster which is an average of 6.16 days. Higher growth rate is an average of 18.14% /etmal. Plant height 3, 4 and 5 higher MST each with an average of 33.81, 38.17 and 42.95 cm. The number of leaves 3, 4 and 5 MST more each with an average of 2.93, 3.60 and 3.93 strands. IVH higher averaging 4.55.